Ujub and Self-Inflation: Reconstructing The Ethical Structure of Abyān Al-Ḥawāij in Dialogue With Contemporary Moral Psychology - Yayan Rubiyanto; Endang Nurhayati; Sri Harti Widyastuti; Wahid Tuftazani Rizqi; Annas Fitria Sa’adah (Dialogium: Journal of Islamic Studies, 2026)
This article examines the concept of ujub in the Nusantara Sufi manuscript Abyān al-Ḥawāij (copied in 1264 H/1848 CE) and analyzes its structural parallels with the phenomenon of self-inflation in contemporary moral psychology. Using a qualitative manuscript-based approach with philological-hermeneutic analysis and structural comparison, the study reconstructs ujub as a coherent ethical structure rather than merely a normative moral prohibition. The findings reveal that ujub in the manuscript is articulated as a condition of evaluative self-inflation characterized by exaggerated self-appraisal, asymmetrical attribution of success, moral superiority, and illusion of spiritual autonomy. These structural elements resonate with constructs in modern psychology, including self-enhancement bias, overconfidence bias, self-serving bias, and moral superiority illusion. However, while psychological theories frame these tendencies within cognitive-regulatory and adaptive functions, Abyān al-Ḥawāij situates them within a theological-ethical horizon emphasizing humility and awareness of human dependence on the Divine.This study contributes to comparative moral psychology by positioning a Nusantara Sufi manuscript as a conceptual source for interdisciplinary dialogue. It demonstrates that classical Islamic ethical texts contain systematic moral analysis compatible with contemporary theoretical discourse, while maintaining distinct epistemological foundations. The findings also offer implications for Islamic education, suggesting that moral cultivation should integrate spiritual discipline with awareness of cognitive mechanisms underlying self-inflation